Influence of Emotional Intelligence on Job Satisfaction: Moderating Effect of Organisational Commitment - MBWAGA, TEDDY BONIFACE; Tefurukwa, Oscar W. (Journal of Policy and Leadership, 2024)
<span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*351.69px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.835918);" role="presentation">Job satisfaction has received much attention as a positive HRM requirement. Tanzania has <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*367.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.763572);" role="presentation">made <span dir="ltr" style="left: calc(var(--scale-factor)*97.79px); top: calc(var(--scale-factor)*367.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.792132);" role="presentation">several <span dir="ltr" style="left: calc(var(--scale-factor)*140.48px); top: calc(var(--scale-factor)*367.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.78858);" role="presentation">efforts <span dir="ltr" style="left: calc(var(--scale-factor)*179.21px); top: calc(var(--scale-factor)*367.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.774772);" role="presentation">to <span dir="ltr" style="left: calc(var(--scale-factor)*196.60px); top: calc(var(--scale-factor)*367.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.773923);" role="presentation">enhance <span dir="ltr" style="left: calc(var(--scale-factor)*244.46px); top: calc(var(--scale-factor)*367.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.838491);" role="presentation">job <span dir="ltr" style="left: calc(var(--scale-factor)*267.85px); top: calc(var(--scale-factor)*367.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.804113);" role="presentation">satisfaction <span dir="ltr" style="left: calc(var(--scale-factor)*331.40px); top: calc(var(--scale-factor)*367.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.769565);" role="presentation">by <span dir="ltr" style="left: calc(var(--scale-factor)*350.71px); top: calc(var(--scale-factor)*367.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.799251);" role="presentation">fostering <span dir="ltr" style="left: calc(var(--scale-factor)*401.45px); top: calc(var(--scale-factor)*367.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.763704);" role="presentation">commitment, <span dir="ltr" style="left: calc(var(--scale-factor)*471.02px); top: calc(var(--scale-factor)*367.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.797181);" role="presentation">improved <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*383.37px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.782628);" role="presentation">performance and ultimately leading to higher production. Even with the efforts made, <span dir="ltr" style="left: calc(var(--scale-factor)*470.62px); top: calc(var(--scale-factor)*383.37px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.826566);" role="presentation">empirical <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*399.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.830893);" role="presentation">studies reveal that job satisfaction levels of staff in the public sector are generally low and <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*415.17px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.812999);" role="presentation">unsatisfactory, consequently triggering an increase in labour turnover and low performance. <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*431.03px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.807392);" role="presentation">Extant studies have yet to cover all the factors influenc<span dir="ltr" style="left: calc(var(--scale-factor)*333.19px); top: calc(var(--scale-factor)*431.03px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.817382);" role="presentation">ing job satisfaction. Thus, the current <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*446.87px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.797913);" role="presentation">study examined the influence of emotional intelligence on job satisfaction, with organisational <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*462.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.812694);" role="presentation">commitment as a moderating variable. A correlational research design was employed, and a <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*478.67px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.78594);" role="presentation">simple random sampling techniqu<span dir="ltr" style="left: calc(var(--scale-factor)*224.93px); top: calc(var(--scale-factor)*478.67px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.770867);" role="presentation">e was used to select 108 respondents from a target population <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*494.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.867736);" role="presentation">of 148 employees. Data were analysed using Structural Equation Modelling (SEM). The <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*510.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.794328);" role="presentation">findings reveal that interpersonal skills positively affect normative commitment (β=0.244), job <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*526.19px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.798865);" role="presentation">satisfaction (<span dir="ltr" style="left: calc(var(--scale-factor)*125.78px); top: calc(var(--scale-factor)*526.19px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.778603);" role="presentation">β=0.156), and affective commitment (β=0.303) but negatively impact continuance <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*542.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.776765);" role="presentation">commitment (β=-<span dir="ltr" style="left: calc(var(--scale-factor)*147.86px); top: calc(var(--scale-factor)*542.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.78961);" role="presentation">0.29). Empathetic response shows positive effects on normative commitment <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*557.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.800419);" role="presentation">(β=0.353), continuance commitment (β=0.39), and job satisfaction (β=0.123), yet negative<span dir="ltr" style="left: calc(var(--scale-factor)*507.82px); top: calc(var(--scale-factor)*557.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.830681);" role="presentation">ly <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*573.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.793947);" role="presentation">affecting <span dir="ltr" style="left: calc(var(--scale-factor)*114.32px); top: calc(var(--scale-factor)*573.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.778665);" role="presentation">affective <span dir="ltr" style="left: calc(var(--scale-factor)*163.37px); top: calc(var(--scale-factor)*573.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.764091);" role="presentation">commitment <span dir="ltr" style="left: calc(var(--scale-factor)*230.54px); top: calc(var(--scale-factor)*573.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.807146);" role="presentation">(β=-<span dir="ltr" style="left: calc(var(--scale-factor)*252.77px); top: calc(var(--scale-factor)*573.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.793087);" role="presentation">0.105). <span dir="ltr" style="left: calc(var(--scale-factor)*295.24px); top: calc(var(--scale-factor)*573.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.856355);" role="presentation">Mood <span dir="ltr" style="left: calc(var(--scale-factor)*331.71px); top: calc(var(--scale-factor)*573.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.82041);" role="presentation">regulation <span dir="ltr" style="left: calc(var(--scale-factor)*390.24px); top: calc(var(--scale-factor)*573.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.797166);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*416.75px); top: calc(var(--scale-factor)*573.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.785269);" role="presentation">self-<span dir="ltr" style="left: calc(var(--scale-factor)*437.47px); top: calc(var(--scale-factor)*573.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.79007);" role="presentation">awareness <span dir="ltr" style="left: calc(var(--scale-factor)*496.61px); top: calc(var(--scale-factor)*573.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.824227);" role="presentation">also <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*589.67px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.791737);" role="presentation">demonstrate significant impacts, with internal motivation positively influencing job satisfaction <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*605.66px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.779236);" role="presentation">(β=0.211) and affective commitment (β=0.144) but negatively affecting no<span dir="ltr" style="left: calc(var(--scale-factor)*418.87px); top: calc(var(--scale-factor)*605.66px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.76982);" role="presentation">rmative commitment <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*621.50px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.807146);" role="presentation">(β=-<span dir="ltr" style="left: calc(var(--scale-factor)*85.94px); top: calc(var(--scale-factor)*621.50px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.858073);" role="presentation">0.252). Based on the findings, there is a need to deliberately consider performance <span dir="ltr" style="left: calc(var(--scale-factor)*63.84px); top: calc(var(--scale-factor)*637.34px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.790035);" role="presentation">management of emotional intelligence to improve job satisfaction and increase commitment.